2014
DOI: 10.1094/pdis-05-13-0498-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Colletotrichum karstii Causing Glomerella Leaf Spot on Apple in Santa Catarina State, Brazil

Abstract: Glomerella leaf spot (GLS) is an emerging disease of apple (Malus domestica Borkh.) that has been reported in regions with a humid subtropical climate, such as southern Brazil, the southeastern United States, and more recently eastern China. GLS is favored by high humidity and temperatures between 23 and 28°C and can result in extensive defoliation when the severity is high. The disease was first reported 1988 in Brazil on cvs. Gala and Golden Delicious in orchards in Paraná State (3), but now is widespread in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…These histological observations demonstrate that C. fructicola causes GLS in a typical hemibiotrophic manner. Similarly, by electrolyte leakage assay, Velho et al (2016) indirectly revealed that C. fructicola serves as a hemibiotrophic fungus, with a biotrophic stage that lasts at least 24 hr. In the present study, ultrastructural results showed that the biotrophic stage could last at least 36 hr.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These histological observations demonstrate that C. fructicola causes GLS in a typical hemibiotrophic manner. Similarly, by electrolyte leakage assay, Velho et al (2016) indirectly revealed that C. fructicola serves as a hemibiotrophic fungus, with a biotrophic stage that lasts at least 24 hr. In the present study, ultrastructural results showed that the biotrophic stage could last at least 36 hr.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, the disease was first found in Georgia in 1970 and named in eastern Tennessee in 1998 (Taylor, ; González and Sutton, ). In Brazil, the disease was widely reported in the main apple‐producing areas of the country (Velho et al , ). In China, GLS was first reported in Jiangsu Province in 2011 (Wang et al , ) and thereafter has been documented in seven major apple production provinces, covering almost all apple‐producing areas (Wang et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…, Velho et al. ). The disease resulted in up to 70% of leaf defoliation of ‘Gala’ (Camilo and Denardi ).…”
mentioning
confidence: 99%